Analisis Dinamika dan Faktor Penyebab Perubahan Lahan LP2B: Studi Kasus di Kecamatan Ciseeng, Kabupaten Bogor - Mujio Mujio; Ahmad Faizul Fadli; Edy Mulyadi; Selfi Nor Amalia Istiqomah (Jurnal Zona, 2025)
Land use change in agricultural areas is one of the main challenges in sustainable spatial planning, especially in peri-urban areas. This study aims to analyze the land use change of Sustainable Food Crop Land (LP2B) in Ciseeng District, Bogor Regency. A qualitative descriptive approach was used with primary data from interviews and field observations, supported by spatial and regulatory data. The results of the study indicate that approximately 15.57% of the LP2B area in Ciseeng District has experienced land use change for residential, commercial, and other non-agricultural purposes. The land use change is driven by weak regulatory enforcement, high demand for land due to its proximity to urban areas, and limited protection for farmers. The results of the study conclude that sustainable land management requires synergy between policy enforcement, public awareness, and spatial planning integration